2018
DOI: 10.7150/thno.24336
|View full text |Cite
|
Sign up to set email alerts
|

Comparative profiling of analog targets: a case study on resveratrol for mouse melanoma metastasis suppression

Abstract: Many plant-specialized metabolites have remedial properties and provide an endless chemical resource for drug discovery. However, most of these metabolites have promiscuous binding targets in mammalian cells and elicit a series of responses that collectively change the physiology of the cells. To explore the potential of these multi-functional and multi-targeted drugs, it is critical to understand the direct relationships between their key chemical features, the corresponding binding targets and the relevant b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 54 publications
1
23
0
Order By: Relevance
“…Our lab has previously reported that nucleotides from −170 to +43 constitute the minimal mouse FAK promoter that is responsible for basal FAK transcription (Chen et al, 2018 ). After P-Match analysis, which is a new method for identifying transcription factor (TF) binding sites in DNA sequences, we found that the core promoter region of FAK might contain four USF binding sites, three NFκB/Rel binding sites, two cEts-1/PEA3 binding sites, one GATA1 binding site and one Pax-3 binding site (Supplementary file 2: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our lab has previously reported that nucleotides from −170 to +43 constitute the minimal mouse FAK promoter that is responsible for basal FAK transcription (Chen et al, 2018 ). After P-Match analysis, which is a new method for identifying transcription factor (TF) binding sites in DNA sequences, we found that the core promoter region of FAK might contain four USF binding sites, three NFκB/Rel binding sites, two cEts-1/PEA3 binding sites, one GATA1 binding site and one Pax-3 binding site (Supplementary file 2: Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To elucidate the mechanism of action of RSV’s antimigration effect on A549 cells, a quantitative chemical proteomics approach was applied to identify the protein targets of RSV in A549 cells, as illustrated in Figure 2 . Briefly, based on the structure-activity relationship of RSV ( Chen et al, 2018 ), we first synthesized an RSV probe (RSV-P) derived from RSV ( Figure 3A ). The structure of RSV-P was validated with NMR and MS ( Supplementary Figures S3, S4 ).…”
Section: Resultsmentioning
confidence: 99%
“…As a result, we identified histone deacetylase I (HDAC1) as the protein target of resveratrol in mouse melanoma cells and revealed an epigenetic regulation pathway of focal adhesion kinase. 41 Other excellent examples are listed in Fig. 3b.…”
Section: Activity-based Probementioning
confidence: 99%
“…With in vivo and in vitro experiments, we confirmed that resveratrol inhibits focal adhesion kinase (FAK) expression by interacting with HDAC1. 41 Although the method has been widely used in protein identification, [112][113][114] it has two disadvantages: (i) some low-abundance but vital target proteins are still invisible after Coomassie brilliant blue staining or even silver staining, resulting in target loss; and (ii) some distinct bands or spots, especially bands, contain more than one protein, so the nonspecific binding in these bands or spots may also be identified.…”
Section: Gel Separation and Band Identificationmentioning
confidence: 99%
See 1 more Smart Citation